Pre-schoolers bronchial asthma in the primary health care centres: physicians’ knowledge and practice in Jazan region Saudi Arabia - Gohal, Gassem Ali; Eltyeb, Ebtihal Elameen (International Journal of Contemporary Pediatrics, 2019)
Background: The aim of this study was to assess the knowledge and practice of primary health care (PHC) physicians in the diagnosis and management of preschoolers’ bronchial asthma in Jazan region in Saudi Arabia. Methods: A survey of 106 primary care physicians practicing in Jazan region was conducted. Domains that assessed include asthma causes, diagnosis, management, and prognosis. Item formats included self-reports through online version questionnaire during the period December 2018 to February 2019. Results: Among 72% of participants were general practitioners, with about 60% were mid-level experience (1-10 years), overall PHC physician level of knowledge and practice was moderate level, and the knowledge was significantly affected by grade of specialty, years of experience, and the number of bronchial asthma patients seen in the last three months in the center. This study showed mis concepts and mal practices of PHC physicians as 57% of them considered prescribing antibiotics during asthma attacks, while 72% agreed that anti-cough therapy is helpful in asthma like symptoms. Conclusions: This study proves that PHC physician in Jazan region are moderately aware of preschoolers’ bronchial asthma if compared to studies done in other regions of Saudi Arabia. There are certain practices and concepts regarding preschooler’s asthma that need to be revised. Raising the awareness regarding adherence to guidelines of pediatrics bronchial asthma mandates more attention and advocacy.